A 54-Year-Old Woman with Donor Cell Origin of Multiple Myeloma after Allogeneic Hematopoietic Stem Cell Transplantation for the Treatment of CML. (18th February 2016) - Maestas, Erika; Jain, Shikha; Stiff, Patrick
Abstract : Chronic myeloid leukemia is a myeloproliferative disorder that may be treated with hematopoietic stem cell transplantation (HSCT). While posttransplantation relapse of disease resulting from a failure to eradicate the patient's original leukemia could occur, patients may also rarely develop a secondary malignancy or myelodysplastic syndrome (MDS) of donor origin termed donor cell leukemia (DCL). Cases of donor-derived acute myeloid leukemia (AML) or MDS after HSCT or solid tumor transplantation have been published. However, very few cases of donor-derived multiple myeloma (MM) exist. We describe a patient who developed a donor-derived MM following allogeneic HSCT from a sibling donor.